Chelation-directed remote meta-C–H functionalization of aromatic aldehydes and ketones. Issue 82 (30th September 2019) - Xie, Shuguang; Li, Sen; Ma, Wenqian; Xu, Xiaohua; Jin, Zhong
Abstract : Chelation-directed remote meta -C–H functionalization of aromatic aldehydes and ketones was realized via in situ -generated acetals and ketals. Abstract : We disclose herein the development of a versatile 1, 2-diol directing template for palladium-catalyzed remote meta -C–H functionalization of aromatic aldehydes and ketones. In situ -generation of acetals and ketals, as well as removal afterwards, makes the C–H bond functionalization process more straightforward and efficient. This also represents the first example of chelation-directed meta -C–H functionalization of aromatic aldehydes and ketones.